Comments on "AVAIL Phosphorus Fertilizer Enhancer: Meta‐Analysis of 503 Field Evaluations" by B.G. Hopkins et al. Agron. J. 110:389–398 (2018). (1st July 2018) - Chien, S.H.; Rehm, G.W.; Grove, J.H.; Edmeades, D.; McBride, R.; Hopkins, Bryan G.; Fernelius, Kaitlynn J.; Hansen, Neil C.; Eggett, Dennis L.
Abstract : Core Ideas: Fixation of fertilizer phosphorus in soils often decreases phosphorus efficiency. Avail has been reported to enhance fertilizer phosphorus efficiency. A review on the effect of Avail on soil phosphorus‐fixation is critically discussed.